The comparison of brain's cortex electrical activity between endurance runners and sedentary men during rest period - نادر علیجانپور; علی کاظمی; مهدی اکبری; حسن عشایری (Shahid Beheshti University, 2014)
The results of some studies show that the first changes happening due to the physical activity in brain are the changes in alpha and beta brain wave activity. These changes are more obvious when individuals are allowed to take part in their favorite activities and the desired intensity for a long time. Therefore, this research aims at studying the comparison of brain cortex electrical activity between endurance runners and sedentary men during rest period. In this research, the researcher has compared changes in dependent variables between experimental and control groups. To do this, ten male endurance runners, with the average age 24/23+2/12, who had participated in National and International competitions and also performed endurance training for at least five years, have been compared with ten sedentary men with the average age 24/21+2/32. The results of this research showed that there was a significant difference between the experimental and control groups in brain cortex alpha and beta waves (p≤0.05). It also showed that there was a significant difference between these two groups in brain cortex lobes alpha wave, especially in occipital lobe and generally in the other lobes. It should be mentioned that the significant difference of beta wave in frontal lobe was seen (p<0.05). In general, it can be concluded that chronic endurance training causes an increase in brain cortex electrical activity (alpha and beta brain waves) and then leads to improvement of alertness, concentration, creativity, visualization, and relaxation.